DEVELOPMENT OF STUDENTS’ WORKSHE DEVELOPMENT OF STUDENTS’ WORKSHEET BASED ON MULTIPLE REPRESENTATION OF ENVIRONMENTAL POLLUTION THEME FOR JUNIOR HIGH SCHOOL - Nur Balqis Mutia (Education Journal : Journal Educational Research and Development, 2022)
This study aims to produce students' worksheet of natural science on environmental pollution material for students of class VII in junior high school that are suitable for learning activities. This study uses the research and development methods by adapting Thiagarajan model through three stages of research that includes define, design and develop. The data collection was done by using observation, interviews and validation of the expert teams. The appropriateness of students’ worksheet is assessed based on aspects of the students’ worksheet component, content appropriateness, presentation, graphics, language and characteristics students’ worksheet based on multiple representations. The result of this research is students’ worksheet based on multiple representations which have been validated by expert team that is expert lecturer, science teacher and colleague. Based on the assessment that has been done by a team of experts, students’ worksheet of science learning based on multiple representations with the theme of environmental pollution categorized very well. To conclude, that students’ worksheet of natural science based on multiple representation is worthy to be used in natural science learning.